An investigation into speaking-in-class anxiety of English-majored students: The case of the second-year students at the School of Foreign Languages, Thai Nguyen university - Trần, Thị Phương (2020)
The present study aims to investigate speaking-in-class anxiety with the main focus on the second-year English-majored students at the School of Foreign Languages, Thai Nguyen university. The specific objectives of the present study are: To examine the levels of speaking-in-class anxiety experienced by the second-year English-majored students at School of Foreign Languages, Thai Nguyen University. To investigate the types of in-class activities which cause the most anxiety to students and which reduce students‟ anxiety. To suggest what teachers‟ behaviors and characteristics can reduce students‟ anxiety in English speaking classroom. The three research questions this study aims to address are as follows: What levels of anxiety the second-year English-majored students manifest in English speaking classrooms? What in-class activities provoke or reduce students’ anxiety in English speaking classrooms? What teachers’ behaviors and characteristics are helpful to reduce students’ anxiety in speaking English?